Common Prognostic Biomarkers and Outcomes in Patients with COVID-19 Infection in Saudi Arabia - Mashael Abujabal; Mohamed A. Shalaby; Layla Abdullah; Amr S. Albanna; Mohamed Elzoghby; Ghadeer Ghazi Alahmadi; Sidharth Kumar Sethi; Mohamad-Hani Temsah; Fadi Aljamaan; Khalid Alhasan; Jameela A. Kari (Tropical Medicine and Infectious Disease, 2023)
Background: COVID-19 is a respiratory disease that eventually became a pandemic, with 300 million people infected around the world. Alongside the improvement in COVID-19 management and vaccine development, identifying biomarkers for COVID-19 has recently been reported to help in early prediction and managing severe cases, which might improve outcomes. Our study aimed to find out if there is any correlation between clinical severity and elevated hematological and biochemical markers in COVID-19 patients and its effect on the outcome. Methods: We have collected retrospective data on socio-demographics, medical history, biomarkers, and disease outcomes from five hospitals and health institutions in the Kingdom of Saudi Arabia. Results: Pneumonia was the most common presentation of COVID-19 in our cohort. The presence of abnormal inflammatory biomarkers (D-dimer, CRP, troponin, LDH, ferritin, and t white blood cells) was significantly associated with unstable COVID-19 disease. In addition, patients with evidence of severe respiratory disease, particularly those who required mechanical ventilation, had higher biomarkers when compared to those with stable respiratory conditions (p < 0.001). Conclusion: Identifying biomarkers predicts outcomes for COVID-19 patients and may significantly help in their management.